Leadership Through Discursive Strategies in Abiy Ahmed’s Welcoming Speech at the 35th Ordinary Session of the African Union Assembly - Srour , Ibrahim (Tecno Scientifica Publisher, 2023)
Diplomatic language and political discourse have always been inseparable and have wielded effects in terms of power, control, and domination. These effects depended on how language was used and for what purpose. The article stems from the premise that the use of specific strategies, particularly discursive strategies, enables users to convey power and leadership. Consequently, this article analyzes the political discourse, specifically the diplomatic language, used in the welcoming speech delivered by Ethiopia's Prime Minister Abiy Ahmed at the African Union (AU) Assembly. The analysis is conducted based on Reisigl and Wodak's Discourse-Historical Approach (DHA) theory, focusing on their five discursive strategies. The goal is to uncover the discursive strategies employed by Abiy Ahmed to achieve unity and, through unity, convey Africa's power in general, in the face of foreign intrusion, as well as Ethiopia's power specifically. The analysis reveals that the discursive strategy of predication predominated throughout the speech, both individually and in combination. Predication was employed to showcase notions of power, positivity, independence, and sovereignty of Ethiopia. By utilizing these discursive strategies, Abiy emphasizes the importance of collaborative efforts to overcome any obstacles that arise in Africa.